Hubungan pengetahuan tentang infeksi menular seksual dengan perilaku seksual pada remaja di 3 SMA wilayah Kabupaten Sukabumi - Heni Haryani (STIKes Karsa Husada Garut, 2014)
Adolescents are very susceptible to sexually transmitted diseases. Lack of reproductive health information especially about prevention of sexually transmitted diseases makes adolescents dare to do sexual intercourse. The purpose of this study to know correlation between knowledge of sexually transmitted diseases and sexual behavior of adolescents. The type of this study is analysis with cross sectional approach. The population of this study were all of students at 3 Senior high school of District Sukabumi consist 1631 students. The sample were used 321 students by proportionated stratified random sampling. The data is primary data from answering the questionnaires. The statistic test is Rank-Spearman test with = 0,05. Based on univariat analysis, knowledge of sexually transmitted diseaseas, good category (67,00%), enough category (32,10%), and low category (0,90%). Sexual behavior good category (81,60%), enough category (15,30%), and bad category (3,10%). Bivariat analysis shown that there was significant correlation between knowledge of sexually transmitted diseases and sexual behavior of adolescents (CC = 0,124, sig = 0,026. There was correlation between knowledge of sexually transmitted diseases and sexual behavior of adolescents